4-dimensional seismic interpretation to monitor CO2 injection in carbon capture & storage project of Sleipner field, North Sea, Norway using inversion method - Brimas Aptanindia Pangestu; Muhammad Lubis (Universitas Islam Riau (UIR) Press, 2023)
Sleipner is the world's first commercial Carbon Capture and Storage (CCS) project, located off the coast of Norway, with the goal of reducing carbon emissions by capturing CO2 and storing it in a utsira saline aquifer sandstone reservoir capable of storing up to 600 billion tonnes of CO2. The CO2 injection in these projects increases year after year, so the CO2 development must be monitored to see the distribution pattern and its implications for the reservoir zone. The purpose of this research is to calculate and model the CO2 distribution resulting from acoustic impedance inversion using 4-dimensional inversion, to calculate the repeatability from seismic data between baseline and monitor using the Normalized Root Mean Square attribute. In the processing, baseline and monitor data must be matched in the overburden zone using a cross-equalization process so that the inversion process. The results revealed a correlation between the two seismic data sets (baseline and monitor) with the classification of Reasonable Repeatability, and CO2 distribution in a securely stored reservoir that spreads laterally and does not leak.